Development of a Superconducting Heat Switch for an Ideal Integrating Bolometer - Mok, Mason (Proceedings of the Wisconsin Space Conference, 2017)
Improving the sensitivity of current state-of-the-art bolometers is essential for future cosmology endeavors. Having a bolometer that is thermally isolated from its thermal sink is ideal in order to reduce phonon noise: the factor limiting bolometer sensitivity. To thermally isolate a bolometer as much as possible a pixel-scale superconducting heat switch is being developed to control the conductance between a bolometer and its thermal sink. The heat switch is comprised of a superconducting thin aluminum film surrounded by a niobium coil. Current is passed through the coil and the resulting magnetic field drives the aluminum into its high conductance normal state. Experimental data agrees well with the results of a thermal model of the device.Â Â